2021
DOI: 10.3390/agronomy11071367
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Long-Term Different Crop Rotations and Monoculture on Weed Prevalence and Weed Seed Content in the Soil

Abstract: Equally effective way to achieve sustainable farming and the challenge set by the European Commission on 20 May 2020: proper crop rotation and thus reduction of the quantity of on-farm chemicals. Long-term stationary field experiments were established in 1966 at Vytautas Magnus University Experimental Station (54°53′ N, 23°50′ E). The study was conducted with intensive, three-course, field rotation with row crops, for green manure crop rotations, and rye monoculture as well during the last 5-year period of a 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Monoculture provides some empty space and untouched resources for weeds [3]. Weeds are adapted for these conditions and will use the resources to grow and produce seeds [22]. Crop rotation disturbs these niches and prevents weeds from finding their place for establishing, thus breaking their cycle [23].…”
Section: Discussionmentioning
confidence: 99%
“…Monoculture provides some empty space and untouched resources for weeds [3]. Weeds are adapted for these conditions and will use the resources to grow and produce seeds [22]. Crop rotation disturbs these niches and prevents weeds from finding their place for establishing, thus breaking their cycle [23].…”
Section: Discussionmentioning
confidence: 99%
“…According to Butkevičienė et al [ 22 ], the research data show that 20.2 to 71.4 thousand weed seeds can be found in 1 m 2 of the cultivated soil in the depth of 0–20 cm. In 1 m 2 of the uncultivated soil (natural meadow) in the depth of 0–15 cm, 4.3 thousand weed seeds were found [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is usually indicated that only a few species compose the highest part of the soil seed bank. The authors indicated that soils are mostly contaminated by the seeds of Chenopodium album L. [ 22 , 40 , 41 ], whose annual decline rates were about 14–41% [ 42 ]. In our research, the seeds of Chenopodium album prevailed in the soil seed bank in the spring of 2020, while in the autumn (2020) and in the spring and autumn of 2021, they comprised from 2.5 to 10.8% of the whole seed bank.…”
Section: Discussionmentioning
confidence: 99%
“…Under the context of each one of these axes, several different techniques and methods have been studied and evaluated within the EU, providing a wide range of management alternatives. The diversification (both in space and in time) of cropping systems includes the adoption of crop rotations, cover crops, intercropping, and landscape arrangement (Błażewicz-Woźniak et al, 2015 ; Giuliano et al, 2016 ; Kuht et al, 2017 ; Weber et al, 2017 ; Dhima et al, 2018 ; Royo-Esnal et al, 2018 ; Scavo et al, 2019 , 2021 ; Butkevičienė et al, 2021 ). Cultivar selection could be based on certain agronomic traits that enhance competitive abilities and can potentially suppress weeds more efficiently (Kokare et al, 2014 ; Karkanis et al, 2016 ; De Vita et al, 2017 ; Rasmussen et al, 2021 ).…”
Section: Reducing the Herbicide Use Sustainablymentioning
confidence: 99%